The influence of BMI on the association between serum lycopene and the metabolic syndrome. Issue 7 (9th February 2016) - Han, Guang-Ming; Soliman, Ghada A.; Meza, Jane L.; Islam, K. M. Monirul; Watanabe-Galloway, Shinobu
Abstract: Overweight and obese individuals have an increased risk of developing the metabolic syndrome because of subsequent chronic inflammation and oxidative stress, which the antioxidant nutrient lycopene can reduce. However, studies indicate that different BMI statuses can alter the positive effects of lycopene. Therefore, the purpose of this study was to examine how BMI influences the association between serum lycopene and the metabolic syndrome. The tertile rank method was used to divide 13 196 participants, aged 20 years and older, into three groups according to serum concentrations of lycopene. The associations between serum lycopene and the metabolic syndrome were analysed separately for normal-weight, overweight and obese participants. Overall, the prevalence of the metabolic syndrome was significantly higher in the first tertile group (OR 38·6 %; 95 % CI 36·9, 40·3) compared with the second tertile group (OR 29·3 %; 95 % CI 27·5, 31·1) and the third tertile group (OR 26·6 %; 95 % CI 24·9, 28·3). However, the associations between lycopene and the metabolic syndrome were only significant for normal-weight and overweight participants ( P <0·05), but not for obese participants ( P >0·05), even after adjusting for possible confounding variables. In conclusion, BMI appears to strongly influence the association between serum lycopene and the metabolic syndrome.